PERBANDINGAN EFEK JANGKA PENDEK DRY NEEDLING DAN STRETCHING OTOT ADDUKTOR HIP UNTUK MENGURANGI KETEGANGAN OTOT ADDUKTOR HIP PADA PELARI - Maryati, Liani Indri; Sudarsono, Ari; Aminoto, Toto; Trioclarise, Rovika; Agustina, Dwi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Muscle tightness is a limited movement due to the adaptive shortening of soft muscle tissues. Runners who has muscle tightness, especially on adductor hip muscles if not fixed, would bring impact to body posture thus giving soreness to the back and hip areas. Measuring hip adductor muscle tightness can be used by passive hip abduction test at 90º of hip flexion. Dry needling and stretching intervension can reduce tightness. Comparing the effect of short term dry needling and hip adductor muscle stretching to reduce hip adductor tightness on runner. Quasi experimental study with two groups, pre test and post test. This study involves two groups that has different treatments. 30 samples are divided into two groups. Interventions are given at one meeting. Data is analyzed with Paired Sample T-test with confident factor of 95% and independent Sample T test. Dry needling group has an average, before and after interventions of 25,67 and 37,59. On stretching group has an average of 27,67 and 36,00. Paired t-test analysis shows P value of both group of 0,000. Independent t-test shows P value of 0,025. .There are impacts shown by both interventions and differences on short term effects of giving dry needling and stretching to hip adductor muscle tightness on runners